The structure of the white water sports market in the French Alps - Antoine Marsac (Revue de Géographie Alpine)
In this article, we aim to demonstrate how the natural resources of the Ubaye Valley have shaped the structure of the white water sports market. Work by associations, beginning with the boom in the pursuit of canoeing in the 1930s, dates back the longest in the valley. It reached its peak at the end of the 1970s, marking the beginning of commercial interest. An analysis of the competitive relationships and strategies of the various stakeholders within the local context shows that the offering is based on a process of “touristification”, encouraging the emergence of competition between the companies. Since the 1980s, the expansion of these businesses in the Ubaye Valley, supported by guides, has largely contributed to the development of the first commercial white water rafting offerings in France. The market has segmented, and now consists of companies trading on the image of a protected valley to differentiate itself from competing destinations.